Eye Tracking Reveals Impaired Attentional Disengagement Associated with Sensory Response Patterns in Children with Autism - Sabatos-DeVito, Maura (J Autism Dev Disord, 2016)
This study used a gap-overlap paradigm to examine the impact of distractor salience and temporal overlap on the ability to disengage and orient attention in 50 children (4–13 years) with ASD, DD and TD, and associations between attention and sensory response patterns. Results revealed impaired disengagement and orienting accuracy in ASD. Disengagement was impaired across all groups during temporal overlap for dynamic stimuli compared to static, but only ASD showed slower disengagement from multimodal relative to unimodal dynamic stimuli. Attentional disengagement had differential associations with distinct sensory response patterns in ASD and DD. Atypical sensory processing and temporal binding appear to be intertwined with development of disengagement in ASD, but longitudinal studies are needed to unravel causal pathways.